Industrialization and rural development in the sagra toledana: midway between the metropolitan area and the innovating territory. - Ricardo Méndez; Juan José Michelini; Isabel Del Río; Juana Rodríguez (Anales de Geografía de la Universidad Complutense, 2006)
The article analyzes the current dynamism of Sagra area, Province of Toledo which is characterized as an emergent space within the regional context due to the high industrial growth rate. In particular it is analyzed the industrial path of this region characterized by a double process of early conformation of a local productive system (endogenous factors) and the metropolitan invasion through the effects of relocation (exogenous factors). After a brief reference to the explanatory theoretical context which allows the explanation of the mentioned processes, a set of indicators is analyzed which shows the emerging character of Castilla - La Mancha. Finally the current industrial dynamism is analyzed from the point of view of sectorial structure and evolution, as well as the strategies applied by the furniture firms —the sector with main tradition in the area— and the promotion of the new industrial areas.